The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1017/s003329170700178x
|View full text |Cite
|
Sign up to set email alerts
|

Differential criterion functioning of alcohol use symptomatology in major depressive disorder?

Abstract: Background. Major depressive disorder (MDD) and alcohol use disorders (AUDs) are among the most prevalent psychiatric disorders and are frequently co-morbid. However, some component of this co-morbidity may be artifactual and arise from the influence of current mental state on self-reports of AUD.Method. This study examined whether past-year MDD is associated with differential criterion functioning (DCF) in reports of AUD symptomatology in male and female participants in the National Epidemiological Survey on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…The findings of this study do not confirm the current DSM‐IV dichotomy between alcohol abuse and dependence and indicate that DSM‐IV alcohol abuse symptoms are not, as a group, milder that dependence symptoms in this sample. These findings are similar to the findings of several IRT analyses of DSM‐III‐R and DSM‐IV AUD symptoms from a variety of predominantly EuroAmerican samples, including adults (Langenbucher et al., 2004) and adolescents (Martin et al., 2006) from inpatient and outpatient addiction treatment programs, community family studies (Krueger et al., 2004), and the NESARC epidemiologic sample (Kahler et al., 2006; Lynskey and Agrawal, 2008; Saha et al., 2006, 2007). Taken together, the results of this study and these other IRT studies are consistent with the notion that alcohol abuse and dependence diagnoses as currently formulated measure the same disorder in both American Indians and EuroAmericans.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The findings of this study do not confirm the current DSM‐IV dichotomy between alcohol abuse and dependence and indicate that DSM‐IV alcohol abuse symptoms are not, as a group, milder that dependence symptoms in this sample. These findings are similar to the findings of several IRT analyses of DSM‐III‐R and DSM‐IV AUD symptoms from a variety of predominantly EuroAmerican samples, including adults (Langenbucher et al., 2004) and adolescents (Martin et al., 2006) from inpatient and outpatient addiction treatment programs, community family studies (Krueger et al., 2004), and the NESARC epidemiologic sample (Kahler et al., 2006; Lynskey and Agrawal, 2008; Saha et al., 2006, 2007). Taken together, the results of this study and these other IRT studies are consistent with the notion that alcohol abuse and dependence diagnoses as currently formulated measure the same disorder in both American Indians and EuroAmericans.…”
Section: Discussionsupporting
confidence: 84%
“…IRT analysis has also been used to examine both past year and lifetime DSM‐IV AUD symptoms in several previous studies of adults and adolescents from epidemiological, community, and treatment samples (Kahler and Strong, 2006; Kirisci et al., 2006; Krueger et al., 2004; Langenbucher et al., 2004; Lynskey and Agrawal, 2008; Martin et al., 2006; Saha et al., 2006). In general, these studies of have found that alcohol abuse and dependence symptoms are intermixed in terms of severity and that AUD symptoms occupied the moderate and severe portions of the severity continuum.…”
mentioning
confidence: 99%
“…That said, it is reasonable to assume that given the extensive process of informed consent and assurances of confidentiality that data were reliable and valid, providing ample information for the current analysis. DCF analyses were exploratory in nature and did not specifically control for alternative factors (either measured or unmeasured) other than the attributes we chose that may have influenced criteria endorsement, such as depression in the case of gender (Lynskey & Agrawal, 2008). Finally, inclusion of individuals 50 to 65 limits our ability to generalize our results to an older adult population 65 and older.…”
Section: Limitationsmentioning
confidence: 99%
“…About one in five women will develop an episode of major depression in their lives (Hasin et al, 2005) and these women are at increased risk to also be engaging in alcohol misuse (Lynskey & Agrawal, 2008). In this study, women who had experienced an episode of major depression in the last year were significantly more likely to have problems related to alcohol use, such as drunk driving, conflicts with others, or job difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol misuse is frequently comorbid with depression in women. For example, data from the National Epidemiologic Survey on Alcohol and Related Conditions (NESARC) showed that women with major depressive disorder were more likely than non-depressed women to report multiple criteria for alcohol abuse and dependence (Lynskey & Agrawal, 2008). Research has also repeatedly found associations of women’s depression with binge drinking.…”
mentioning
confidence: 99%